NG, Eva N. S. & CREZEE, Ineke H. M. Interpreting in Legal and Healthcare Settings: Perspectives on research and training. Amsterdam/Philadelphia, John Benjamins, 2020, 351 pp., ISBN 978-90-272-0504-9 - de Boe, Esther (Hikma, 2022)
.